Structural analysis of PdRh/C and PdSn/C and its use as electrocatalysts for ethanol oxidation in alkaline medium. (8th January 2019) - Fontes, Eric H.; Ramos, Carlos Eduardo D.; Nandenha, Júlio; Piasentin, Ricardo M.; Neto, Almir O.; Landers, Richard
Abstract: The Pd/C, PdRh(50:50)/C and PdSn(50:50)/C nanomaterials were used as electrocatalysts for ethanol (EtOH) oxidation in Direct Ethanol Fuel Cell (DEFC) in an alkaline medium. This work aims to provide a complete physical characterization of the nanomaterials, elucidate the bifunctional mechanism concerning ethanol oxidation reaction and understand the influence of carbon – metal bonding in the electrochemical activity. These nanomaterials were investigated by X-ray photoelectron spectroscopy (XPS) and revealed that the atomic percentage of the surface is different of those obtained by Energy Dispersive X-ray spectroscopy (EDS). Raman spectroscopy showed a bonding between palladium and carbon atoms which can play a decisive role in the performance of the materials. Attenuated Total Reflectance technique coupled to the Fourier Transform Infrared spectroscopy (ATR-FTIR) made possible to investigate the oxidation products originated by the ethanol oxidation, and all the electrocatalysts showed the presence of acetaldehyde, carbonate ions, acetate and carbon dioxide, suggesting that the mechanism of oxidation is incomplete. Among all the nanomaterials studied, PdSn(50:50)/C showed the best electrochemical and Fuel Cell's results. It is about 33% better than Pd/C. The micrographs obtained by Transmission Electron Microscopy (TEM) revealed some agglomerate regions, but they are consistent with the literature data. Highlights: Pd-C bonds show a significant effect toward EOR. XPS was more surface sensitive than EDS concerning metal oxidation states. PdSn(50:50)/C has a better performance in DEFC than Pd/C and PdRh(50:50)/C.